Struggling to define a nation American music and the twentieth century - Garrett, Charles Hiroshi, 1966-; American Council of Learned Societies (Berkeley : University of California Press, 2008)
Identifying music as a vital site of cultural debate, Struggling to Define a Nation captures the dynamic, contested nature of musical life in the United States. In an engaging blend of music analysis and cultur al critique, Charles Hiroshi Garrett examines a dazzling array of genre s--including art music, jazz, popular song, ragtime, and Hawaiian music --and numerous well-known musicians, such as Charles Ives, Jelly Roll M orton, Louis Armstrong, and Irving Berlin. Garrett argues that rather t han a single, unified vision, an exploration of the past century reveal s a contested array of musical perspectives on the nation, each one adv ancing a different facet of American identity through sound.
Charles Ives's Four ragtime dances and true American music -- Jelly Roll Morton and the Spanish tinge -- Louis Armstrong and the great migr ation -- Chinatown, whose Chinatown? Defining America's borders with mu sical orientalism -- Sounds of paradise: Hawai'i and the American music al imagination -- Conclusion: American music at the turn of a new centu ry.
Includes bibliographical references (p. 259-276) and index.
Electronic text and image data.
Keywords: Music -- United States -- 20th century -- History and criticism; Nationalism in music